Establishment and validation of reference intervals for tumor markers (AFP, CEA, CA19‐9, CA15‐3, CA125, PSA, HE4, Cyfra 21‐1, and ProGRP) in primary care centers in Korea: A cross‐sectional retrospective study - Nah, Eun‐Hee; Cho, Seon; Park, Hyeran; Kim, Suyoung; Kwon, Eunjoo; Cho, Han‐Ik (Health science reports, 2023)
Background and Aims The reference interval (RI) for a tumor marker may vary between populations, detection systems, and the methods used to obtain their values. The aims of this study were to establish age‐ and sex‐specific RIs for the following nine common tumor markers and to validate the established RIs in Korean adults: alpha fetoprotein (AFP), carcinoembryonic antigen (CEA), cancer antigen (CA) 19‐9, CA15‐3, CA125, Human epididymis protein 4 (HE4), total prostate specific antigen, cytokeratin fragment (Cyfra) 21‐1, and progastrin‐releasing peptide (ProGRP). Methods This cross‐sectional study consecutively selected 214,159 individuals (aged 18–98 years) who underwent health checkups at 16 health‐promotion centers in 13 Korean cities. Finally, 62,752 examinees were used to establish the RIs after removing outliers. RIs were established using an indirect method according to the CLSI EP28‐A3C guideline. The established RIs were validated by calculating the proportion of individuals outside each RI. Results Sex‐related differences were observed for AFP, CEA, CA19‐9, Cyfra 21‐1, and ProGRP (p < 0.05): AFP, CEA and Cyfra 21‐1 were higher in males, and CA19‐9 and proGRP were higher in females. Most of the tumor markers except CA15‐3 and CA125 increased with age: CA125 decreased at ≥50 years of age (p < 0.05), while CA15‐3 did not vary with age. Less than 5% of subjects were outside all RIs (the 2.5th and 97.5th percentiles) established in the present study. Meanwhile, less than 3% of the healthy reference subjects fell outside the current and manufacturers' RIs of all tumor markers except Cyfra 21‐1. Conclusion This study has determined age‐ and sex‐specific RIs for nine common tumor markers in the healthy Korean population, which could be useful for clinicians making clinical decisions and assessments.